2013
DOI: 10.1111/zoj.12002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the land snail genusAlopia(Gastropoda: Clausiliidae) reveals multiple inversions of chirality

Abstract: Whereas the vast majority of gastropods possess dextral shell and body organization, members of the Clausiliidae family are almost exclusively sinistral. Within this group a unique feature of the alpine genus Alopia is the comparable representation of sinistral and dextral taxa, and the existence of enantiomorph taxon pairs that appear to differ only in their chirality. We carried out a molecular phylogenetic study, using mitochondrial cytochrome c oxidase subunit I (COI) gene sequences, in order to find out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…The deep split between A. straminicollis and A. livida was also shown in the mitochondrial gene tree of Fehér et al. () that furthermore demonstrated that these taxa are among the phylogenetically most distant Alopia taxa. However, Fehér et al.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The deep split between A. straminicollis and A. livida was also shown in the mitochondrial gene tree of Fehér et al. () that furthermore demonstrated that these taxa are among the phylogenetically most distant Alopia taxa. However, Fehér et al.…”
Section: Discussionmentioning
confidence: 61%
“…However, Fehér et al. () did not find that there is nevertheless an extensive exchange of mitochondrial haplotypes between these taxa, likely because they sampled only few specimens per species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effective small population size in terrestrial pulmonates can result in an isolated group of individuals differing merely in chirality, either in alloparty or parapatry. In high‐spired pulmonates, such as the present Cristataria , as well as Alopia , Albinaria (Fehér et al., ; Kornilios et al., ) and Partula (Johnson et al., ), gene flow would continue between enantiomorphic pairs of populations where they meet because of their copulation mode, unless additional reproductive barriers evolve. Such taxon pairs may accordingly represent chiral morphs or subspecies, as suggested in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Using a clock‐like mutation rate of 8.6% per million years, Fehér et al. () estimated that the earliest divergence in Alopia took place between 0.8 and 1.6 million years ago (Mya) during the mid‐Pleistocene. According to the same study, the divergences within the subgenera of Carinigera , Carinigera and Nymphogena , respectively, occurred 2.2–5.0 Mya and 2.3–5.4 Mya, in the late Pliocene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation